Fabrication of Oligomeric Avidin Scaffolds for Valency‐Controlled Surface Display of Functional Ligands. Issue 38 (23rd August 2018) - Yoon, Hye Ryeon; Choi, Hyeongjoo; Choi, Yoon‐Aa; Kim, Jung A.; Jung, Juyeon; Kim, Ho Min; Jung, Yongwon
Abstract: Multivalent surface display of biomolecules is crucial to study and utilize multivalent biological interactions. However, precise valency control of surface‐displayed ligands remains extremely difficult. Now a series of new oligomeric avidin proteins were fabricated that allow facile control of surface multivalency of biotinylated ligands. Naturally dimeric rhizavidin (RA) was engineered to form a mixture of oligomeric avidin assemblies, and discrete RA oligomers from the dimer to octamer of RA, were homogeneously prepared. These oligomeric avidins are in polygonal forms with expected numbers of stable biotin binding sites. Upon immobilization on low‐density biotin‐coated gold surfaces, RA dimer, trimer, and tetramer scaffolds provided accurate mean residual valencies of 2, 3, and 4, respectively, for biotinylated proteins. Valency‐controlled display of antibody binding protein G on these RA surfaces showed clear valency‐dependent enhancement of antibody capturing stability. Abstract : Oligomeric avidin proteins with wide biotin binding valencies ranging from 4 to 16 were developed from naturally dimeric rhizavidin (RA) for valency‐controlled surface display of biotinylated ligands. RA dimer, trimer, and tetramer scaffolds provided accurate mean residual binding valencies of 2, 3, and 4, respectively, for biotinylated proteins.